INTERKULTURELLES TRAINING IM DAF-UNTERRICHT KRITISCHE VORFÄLLE ALS TRAININGSMODELL FÜR ALGERISCHE DAF-STUDIERENDEN - Khaled Brahim (Studii de gramatică contrastivă, 2025)
Today’s teaching of German as foreign language (DaF) goes beyond working on language skills to the acquisition of intercultural competence. This competence is now considered as one of the strategic learning activities in connection with the importance of regional studies and culture, which can deliver a cultural image of the target language country when learning a foreign language. Meanwhile there is still indecision about using methods and strategies to acquire intercultural competence in Algerian DaF courses, which raises the question of the availability of appropriate strategies for intercultural training. In this context, this article presents intercultural training methods such as Culture Assimilator and its tasks such as Critical Incidents in a learning scenario, which can optimize the intercultural competence of Algerian German as foreign language students.